When is the best time to give birth? - Sylvia Frühwirth-Schnatter; Christoph Pamminger; Andrea Weber; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2014)
Using Bayesian Markov chain clustering analysis we investigate career paths of Austrian women after their first birth. This data-driven method allows characterizing long-term career paths of mothers over up to 19 years by transitions between parental leave, non-employment and different forms of employment. We, thus, classify women into five cluster-groups with very different long-run career costs of childbearing. We model group membership with a multinomial specification within the finite mixture model. This approach gives insights into the determinants of the long-run family gap. Giving birth late in life may lead very diverse outcomes: on the one hand, it increases the odds to drop out of labor force, and on the other hand, it increases the odds to reach a high-wage career track.
Keywords: 330; fertility; timing of birth; family gap; Transition Data; Markov Chain Monte Carlo; Multinomial Logit; Panel Data